RANCANG BANGUN MANAJEMEN TRANSAKSI PADA BASIS DATA TERDISTRIBUSI BERBASIS WEB SERVICE UNTUK APLIKASI MUSRENBANG (Studi Kasus : Kantor Desa Bulila Kecamatan Telaga) - , Tajuddin Abdillah, S.Kom, Dr. Techn. Ahmad Ashari, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Basically, Musyawarah Perencanaan Pembangunan (MUSRENBANG) is a Bottom Up Planning, which comes from the society to fulfil their needs and wants. Currently, the data of Musrenbang from various places in the Gorontalo District are archived in each village, subdistrict and authoritative SKPD manually, so that losses and damages are often occurred to the data of Musrenbang result from previous years. Furthermore, it is very difficult to Bappeda who take the responsibility for the planning activities in the area to meet the requests of data and information from the legislative and executive bodies. In this research, the researcher created and developed an application that is able to perform transaction management for distributing data of Musrenbang result to the subdistrict and authoritative SKPD based on the web service. The method of this research consists of: interview, literature study related to the concept of web service, analysis and development of transaction management procedures, implementation of the design into programming language and DBMS, and testing of the implementation result. The result of this research showed that the client application built for Musrenbang system is able to perform the transaction management, to ensure the consistency of data stored in every database. The web service application is able to isolate transactions that run concurrently. The client application in Bappeda is able to read data at the databases of every subdistrict and authoritative SKPD.